STRATEGI MEMBANGUN KOMUNIKASI UNTUK PENINGKATAN PENGEMBANGAN KAWASAN PARIWISATA DI KECAMATAN BANJARMASIN UTARA KOTA BANJARMASIN - Bahdiah Bahdiah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
This study aims to analyze communication strategies to enhance tourism development in North Banjarmasin District, Banjarmasin City. The focus of the study is directed at communication patterns between the government, the private sector, and the community in supporting the development of the Sungai Jingah tourist area and the factors that influence its success. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, documentation, and literature studies. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions and verification with validity tests through triangulation. The results show that effective communication between the government, the private sector, and the community is a crucial factor in tourism area development. Synergy between stakeholders plays a role in identifying tourism potential, developing attractions, promoting destinations, and organizing tourism events that have an impact on increasing tourist visits and the local economy. However, tourism area development still faces obstacles such as limited infrastructure, suboptimal coordination between stakeholders, and less than optimal promotional and investment support. Therefore, a more integrated and collaborative communication strategy is needed to support sustainable tourism development in the area.